Pengaruh Kesadaran Diri, Pengaturan Diri, Motivasi, Empati, Dan Keterampilan Sosial Terhadap Kinerja Auditor Pada Kap Di Kota Palembang - Hendra Sastrawinata (SOSIALITA, 2011)
This study aims to: Knowing The Empirical Effect of Self-Awareness, Self Setting, Motivation, Empathy, and Social Skills Performance In Simultaneous Against Auditors And Knowing The Empirical Effect of Self- Awareness, Self Setting, Motivation, Empathy, and Social Skills Performance In Partial Against Auditors. Type of data used in this study is the primary data. Primary data in this study were processed and the data collected by the researcher through the deployment questionnaire. In this study, the population used is the auditor in the Office of KAP which is 8 KAP. Determination of the sample using a convenience sampling method. Based on the results of research and discussion, it can diamabil conclusions as follows: 1. Self- regulation, motivation, empathy and social skills KAP auditors had no significant effect on the performance of partial KAP auditors with independent variables of significance p> 0.05. 2. Self-awareness, self-setting, motivation, empathy and social skills KAP auditors to simultaneously have a significant effect on the performance of KAP auditors in Palembang, where the calculated F value of 50 258 and 0000 of significance (p <0.05) and R Square of 0937.